2012
DOI: 10.3343/alm.2012.32.5.339
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Levels of Interleukins 6, 8, and 10, Tumor Necrosis Factor Alpha, and Granulocyte-colony Stimulating Factor in Korean Burn Patients: Relation to Burn Size and Postburn Time

Abstract: BackgroundMajor burn injury induces an inflammatory response that is accompanied by the release of various cytokines. We investigated the gradual changes in the levels of pro-inflammatory and anti-inflammatory cytokines following burn injury and determined the relationship between these levels and burn size in adult Korean patients with burn injury.MethodsBlood samples from 9 healthy controls and 60 Korean burn patients were collected on days 1, 3, 7, 14, and 21 after burn injury, and concentrations of interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
(41 reference statements)
3
26
0
1
Order By: Relevance
“…A correlation exists between MDA and TNF-α in liver during burns (35) as well as between plasma TNF-α concentration and the degree of thermal damage (36). Similar data have been obtained in clinical and experimental investigations of thermal injury (37,38). But there are contradictory data about the changes of tissue and plasma TNF-α levels.…”
Section: Discussionsupporting
confidence: 75%
“…A correlation exists between MDA and TNF-α in liver during burns (35) as well as between plasma TNF-α concentration and the degree of thermal damage (36). Similar data have been obtained in clinical and experimental investigations of thermal injury (37,38). But there are contradictory data about the changes of tissue and plasma TNF-α levels.…”
Section: Discussionsupporting
confidence: 75%
“…In this regard, other authors have also observed different levels of expression of IL-6 and IL-10 in inflammatory-related pathological situations. As example, Kim et al showed differences in IL-10 and IL-6 levels in the postburn time course [46]. Moreover, in human macrophages, different sensitivities of IL-6 and IL-10 signalling towards the feed-back inhibitor suppressor of cytokine signalling 3 (SOCS3) was reported, suggesting the possibility of different regulation of IL-6 and IL-10 production and, therefore, showing possible differences in the frame of the inflammatory response [47].…”
Section: Discussionmentioning
confidence: 99%
“…Based on experimental models of inflammation, early expressions of TNF-α, IL-6, and IL-1β occur and play key roles. The release of pro-inflammatory mediators such as interferon-γ, TNF-α, IL-6, and IL-8 are increased in burn patients with major burn injury [27,28]. This study shows that low intensity laser therapy has a remarkable effect that inhibits TNF-α and IL-6 levels along with the reduction of edema and inflammatory responses.…”
Section: Discussionmentioning
confidence: 73%